2020
DOI: 10.1002/cpp.2458
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, empathy, negative affect and physical symptoms in patients with asthma

Abstract: Although alexithymia has been found to be associated with physical symptoms in psychosomatic disorders such as asthma, mechanisms linking this association are unknown. However, affective alexithymic features may be associated with physical symptoms in the presence of deficits in affective characteristics such as low empathy and high negative affect. This study aimed to assess direct effects of alexithymic traits on physical symptoms and indirect effects of these subscales through empathy and negative affect (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…All 21 items are scored from 0 to 3. Cronbach's alpha for the Persian scale was good in previous studies (Ghorbani, Khosravani, Mohammadzadeh, & Shadnia, 2019; Khosravani, Samimi Ardestani, Alvani, & Amirinezhad, 2020) and in the present research (0.66 and 0.76).…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…All 21 items are scored from 0 to 3. Cronbach's alpha for the Persian scale was good in previous studies (Ghorbani, Khosravani, Mohammadzadeh, & Shadnia, 2019; Khosravani, Samimi Ardestani, Alvani, & Amirinezhad, 2020) and in the present research (0.66 and 0.76).…”
Section: Methodssupporting
confidence: 81%
“…Simply put, distress intolerance and positive metacognitions are positively related to urgency states (i.e., alcohol craving), while negative alcohol metacognitions and alcohol craving are positively linked to long‐term problematic alcohol use in users experiencing high negative affect. Evidence also has reported that negative and positive alcohol‐related metacognitions were the strongest predictors of problematic alcohol use (Spada & Wells, 2010) and alcohol craving (Khosravani et al, 2020), respectively. Other studies have also shown different associations between alcohol‐related metacognitions and a continuum of drinking behaviours, including urgency states (craving) and problematic alcohol use, respectively (Caselli & Spada, 2010, 2015; Gierski et al, 2015; Khosravani, Zandifar, et al, 2019; Spada & Wells, 2009, 2010), especially in the presence of negative affect (Nikčević et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies, usually non-clinical trials, have reported a correlation between alexithymia and multiple somatization interventions. Not all patients with MUPS have alexithymic features of the same magnitude; thus, the prognosis of patients with severe alexithymia is considered to be less positive than that of patients who have milder alexithymia [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a great number of proposed adaptations to other languages. The most recent examples include Spain [ 56 ], Turkey [ 57 ], Iran [ 58 ], Italy [ 59 ], Peru [ 24 ], Belgium [ 60 ], and China [ 61 ], among others. According to the number of publications, two main authors are highlighted for having a high number of studies reported in which they have used the BES.…”
Section: Resultsmentioning
confidence: 99%